The Past is Another Country - Murray Pratt (PORTAL: Journal of Multidisciplinary International Studies)
This reflective piece explores the formative years of the Institute for International Studies (IIS) at the University of Technology Sydney, considering its approach to global education and immersive learning. Through a critical reflection on the cultural and social context of early 2000s Australia, I recall the collaborative and experimental pedagogies that shaped both students and faculty. By embracing cultural difference, contextualisation, and student-centered inquiry, IIS cultivated a unique educational environment that encouraged exploration beyond conventional academic borders, ultimately laying the foundation for reimagining International Studies in a transformative way.